Response of Lipids and Lipoproteins to Regular Aquatic Endurance Exercise: A Meta-Analysis of Randomized Controlled Trials - Igarashi, Yutaka; Nogami, Yoshie (Journal of Atherosclerosis and Thrombosis, 2019)
Aim: No meta-analysis has examined the effect of regular aquatic endurance exercise on lipid and lipoprotein levels. The purpose of the current work was to perform a meta-analysis to evaluate the effects of regular aquatic endurance exercise on lipid and lipoprotein levels.Methods: The inclusion criteria of the randomized controlled trials were healthy adults in an exercise group performing regular aquatic exercise and a control group not exercising, with a description of the serum high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol, or triglyceride levels provided. The net change in the lipid and lipoprotein levels was calculated from each trial, and the changes in the lipid and lipoprotein levels were pooled using a random effects model.Results: The meta-analysis examined 10 trials involving aquatic endurance exercise and 327 subjects. The pooled net changes in HDL-C, LDL-C, and total cholesterol improved significantly (HDL-C, 4.6 mg/dL; LDL-C, －10.1 mg/dL; total cholesterol, －8.5 mg/dL). When trials were limited to those involving only women, the pooled net changes in HDL-C, LDL-C, and total cholesterol improved significantly. When trials were limited to those involving subjects with a mean age ＜60 years, the pooled net changes in HDL-C, total cholesterol, and triglyceride improved significantly. When trials were limited to those with dyslipidemia, the pooled net changes in HDL-C, LDL-C, total cholesterol, and triglyceride improved significantly.Conclusions: Aquatic endurance exercise improved the lipid and lipoprotein levels and benefited women, middle-aged subjects, and patients with dyslipidemia in particular.